MENDESKRIPSIKAN KEHIDUPAN TOLERANSI BERAGAMA DESA SIKAKAP MELALUI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA - Umam, Muhamad Safiul (Jurnal IKA, 2023)
The residents of Sikakap Village adhere to three major religions, namely, Christianity, Islam and Catholicism (Sikakap in the data). This research aims to "Describe the Life of Religious Tolerance in Sikakap Village Through the Project for Strengthening the Profile of Pancasila Students". The method used is a field survey with structured interview techniques, participant observation, literacy studies, and documentation studies. The sample consisted of five people with a sampling technique using snow ball sampling. The portrait of the life of religious tolerance is included in the category of active tolerance (Rumudan R., Faustina C.P., I Made A., Humaira M). This is illustrated through the realization of social construction as a forum for religious tolerance in society, including: (1) providing comfort to families who are experiencing disaster, easing the burden on families by working together to make coffins and dig graves; (2) providing a food menu during punen, Muslim residents enjoy chicken meat and non-Muslim relatives enjoy pork dishes; (3) the committee distributes sacrificial meat to all groups of people; and (4) non-Muslim brothers follow the halal bi halal tradition during Eid al-Fitr, and Muslim brothers wish non-Muslim brothers a Merry Christmas and New Year.